2019
DOI: 10.1002/celc.201901689
|View full text |Cite
|
Sign up to set email alerts
|

An Ordered Mesoporous Carbon Nanofiber Array for the Sensitive Electrochemical Detection of Malachite Green

Abstract: The recycling of environmental wastes to produce value‐added materials is an attractive prospect for both economic and social development. Herein, we use natural crab shell as the templates to synthesize ordered mesoporous carbon nanofiber arrays (OMCNs) based on a combined hard‐templating and surfactant self‐assembly approach. The Brunauer‐Emmett‐Teller surface area of the OMCNs is calculated to be 1200 m2 g−1, which is accompanied by good conductivity and a mesoporous structure. The as‐prepared OMCNs exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As shown in Figure 3b, the chronocoulometry curves of the charge (Q) with respect to time were used to calculate the active surface areas of the modified electrodes according to the Cottrell equation Eq. : [17] truenormalQ4pt()t=2nFAcD1/2t1/2π1/2+Qdl+Qads …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3b, the chronocoulometry curves of the charge (Q) with respect to time were used to calculate the active surface areas of the modified electrodes according to the Cottrell equation Eq. : [17] truenormalQ4pt()t=2nFAcD1/2t1/2π1/2+Qdl+Qads …”
Section: Resultsmentioning
confidence: 99%
“… ( a ) Cyclic voltammograms of 25 μM malachite green in 0.05 M H 2 SO 4 on the ordered mesoporous carbon nanofiber arrays on glassy carbon (red line) and glassy carbon (black line), with the scan rate = 100 mVs −1 and ( b ) Nyquist plots corresponding to the glassy carbon and ordered mesoporous carbon nanofiber arrays on glassy carbon surface in 5 mM Fe(CN) −3 / −4 +0.1 M KCl [ 85 ]. …”
Section: Figurementioning
confidence: 99%
“…The sensor performance achieved a low LOD of 5.96 µM, a wide linear range of 9.9-280.5 µM, and a good sensitivity of 2.1969 µA/µmol dm −3 . Yang et al [85] demonstrated the utilization of a natural crab shell as a template to synthesize ordered mesoporous carbon nanofiber arrays to prepare an electrochemical sensor for the dye malachite green by DPV. Crab shell has been used as a biological template for generating hierarchical structures, allowing the recycling of environmental waste to produce value-added materials.…”
Section: Animal-derived Wastementioning
confidence: 99%
“…Recently, conductive MOF (CMOF) nanomaterials have become a hot spot in electrochemical area, which is ascribed to high electrical conductivity besides other already known properties of MOFs. , The CMOFs were constructed by linking fully conjugated aromatic ligands with transition-metal centers (e.g., Cu­(II), Ni­(II), and Co­(II)), in which the stacked π-conjugated nanostructures promote charge transfer. It has been found that the same CMOF materials with physical forms have very different properties due to their different microstructures. Moreover, the electrocatalytic and electrochemical sensing properties of the same series of conductive MOFs with different metal atomic centers also differ . For the linkers, a tricatecholate with a highly conjugated structure, 2,3,6,7,10,11-hexahydroxy­triphenylene (H 12 C 18 O 6 , HHTP), is redox-active and capable of reversible interconversions among catecholate, quinone, and semiquinonate, making it have a variety of applications in electrocatalysis, , charge storage, , and chemical resistance sensing. The M 3 (HHTP) 2 nanorod materials based on an electrochemically active metal as the metal center are expected to show high electrocatalytic activity for construction of electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%